Welfare Disparities in Transition Economies: Case of Estonia - Helje Kaldaru; Viktor Trasberg (European Regional Science Association (ERSA), 2001)
The purpose of the article is to analyze the changes in income distribution in transitional societies and show the impact of income disparities on economic growth and social development. Particularly the article analyses the income differences by the sectors and regions of Estonia. A decade ago substantial disparities in income were considered mainly as a problem of developing countries. In communist societies income distribution was considerably more equal despite the fact that average income level was much lower than in the Western welfare states. The situation in the former communist countries significantly changed after reforms began in the early 90s, when a large differentiation by income and wealth rapidly took place. Theoretically, the uneven income distribution has been considered as a supportive factor to economic growth. Recent empirical research (as well as the analyses done by the authors) generally does not confirm that. The authors emphasize that considerable differences in income are considered as "unfair" by large groups of the population. The result might be destabilization in society and low economic growth. Also a human factor plays a more important role than it was assumed earlier. In fact, high technology transfers to the transitional countries support economic growth. However, production efficiency cannot be achieved without a highly qualified and motivated labor force. Large differences in income often benefit a limited number of highly qualified professionals but ruin the morale and eventually qualifications of large groups of employees. As a conclusion, the transitional economies have to decrease income and regional disparities to maintain sustainable growth.
Keywords: 330